Copper (II) and Silver (I) Complexes with bis Schiff Base Ligand: Synthesis, Spectral Characterization and Thermal Studies - Ahmed Razzaq Ibrahim (Journal of Global Pharma Technology, 2018)
Metal complexes of the bis Schiff base (BSAA) ligand, synthesized via condensation 4-amino antipyrine with 4-(4-dimethylamino) benzalidene amino) benzaldehyde which has synthesized from condensation p-amino benzaldehyde and p-dimethyl amino benzaldehyde, are synthesized from nitrate salts of Cu(II) and Ag(I) with ligand in ethanol. The metal complexes and ligand are characterized o86n the basis of elemental analyses, melting point, molar conductance, UV –Vissible , FTIR and thermo gravimetric analysis. The molar conductance data revel that the metal chelates of the ligand with Cu (II) and Ag (I) are electrolytes. From the suggest that the concent sites were proven to be through oxygen of the ring and Nitrogen of the azomethine group.Keywords: 4-aminoantipyrine, copper, Silver, TGA